2000
DOI: 10.1093/oxfordjournals.molbev.a026387
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Cyclin-Dependent Kinases (CDKs) and CDK-Activating Kinases (CAKs): Differential Conservation of CAKs in Yeast and Metazoa

Abstract: Cyclin-dependent kinases (CDKs) function as central regulators of both the cell cycle and transcription. CDK activation depends on phosphorylation by a CDK-activating kinase (CAK). Different CAKs have been identified in budding yeast, fission yeast, and metazoans. All known CAKs belong to the extended CDK family. The sole budding yeast CAK, CAK1, and one of the two CAKs in fission yeast, csk1, have diverged considerably from other CDKs. Cell cycle regulatory components have been largely conserved in eukaryotes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
89
0
3

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(100 citation statements)
references
References 71 publications
8
89
0
3
Order By: Relevance
“…One YAC in this region, Y39G10, could rescue the embryonic lethality of ax224. This YAC was shown previously to contain C. elegans cdk-7 (25). Two lines of evidence confirmed that ax224 is an allele of cdk-7.…”
Section: Identification Of Ax224 An Allele Of C Elegans Cdk-7supporting
confidence: 74%
See 1 more Smart Citation
“…One YAC in this region, Y39G10, could rescue the embryonic lethality of ax224. This YAC was shown previously to contain C. elegans cdk-7 (25). Two lines of evidence confirmed that ax224 is an allele of cdk-7.…”
Section: Identification Of Ax224 An Allele Of C Elegans Cdk-7supporting
confidence: 74%
“…This study revealed no C. elegans orthologue of yeast Cak1͞Civ1, but identified a single CDK7 orthologue, cdk-7 (25). We have isolated a temperaturesensitive mutation in cdk-7, and have used it to study cdk-7 function in the early embryo.…”
mentioning
confidence: 99%
“…(It is not clear whether CTK1 is the actual ortholog of CDK9. A detailed study of evolutionary relationships among CDKs extant in sequence databases of humans, Drosophila melanogaster, and several simpler eukaryotes suggests that the yeast protein closest to human and Drosophila CDK9 is Bur1 [Liu and Kipreos 2000]. The analysis further suggests that yeast Ctk1 is most related to two uncharacterized human proteins, gi|14110386| and gi|20521690|, and one uncharacterized Drosophila protein, gi|24668141|.)…”
Section: What We Do and Do Not Know: A Working Model Of Ctd Phosphorymentioning
confidence: 99%
“…Such charged, non-consensus repeats are not found in the yeast CTD, and our probe therefore is an analogue of the proximal half of the mammalian CTD. The kinase we used, CTDK-I (34 -36), is homologous to human P-TEFb (45) and to other biochemically uncharacterized human open reading frames (46). In view of the sequence relatedness and because CTDK-I and P-TEFb are both involved in phosphorylating RNAP II for elongation (47,48), the pattern of phosphates on our probe is expected to be very similar to that generated on the consensus repeats of the human CTD by P-TEFb or other elongation-related CTD kinases.…”
Section: The Approachmentioning
confidence: 99%